Origin of static magnetic field induced quality improvement in sea bass (Lateolabrax japonicus) during cold storage: Microbial growth inhibition and protein structure stabilization - Tong, Li; Tang, Haiqing; Chen, Jingyi; Sang, Shangyuan; Liang, Ruiping; Zhang, Zhepeng; Ou, Changrong (Frontiers in Nutrition, 2022)
To explore the potential application of static magnetic field (SMF) in marine fish preservation, the sea bass (Lateolabrax japonicus) was exposed to SMF (5 mT) and its quality changes during cold storage were evaluated by total viable counts, water holding capacity, pH, color, and textural properties. Characteristics of the protein in the presence of SMF was investigated by measuring total SH content, Ca2+-ATPase activity, secondary structure, and muscle microstructure. SMF treatment exhibited positive effects on fish quality, showing favorable performance on most fish-quality indicators, especially a significant reduction in the microbial counts. Furthermore, higher total SH content and Ca2+-ATPase activity were observed in SMF-treated samples, demonstrating that the oxidation and denaturation of myofibrillar protein (MP) were delayed due to SMF treatment. The transformation of α-helix to random coil was prevented in SMF-treated samples, indicating that the secondary structure of MP was stabilized by SMF treatment. The above changes in protein structures were accompanied by changes in muscle microstructure. More intact and compact structures were observed in SMF-treated samples, characterized by well-defined boundaries between myofibers. Therefore, our findings suggest that SMF treatment maintained the quality of fish mainly by inhibiting the growth of microorganisms and enhancing the stability of protein structures, and could be an auxiliary technology for preservation of aquatic products.